The Shannoniella sisters (Diptera: Rhinophoridae) - Nihei, Silvio S.; Andrade, Marcos R.; Pape, Thomas; Cerretti, Pierfilippo (Zootaxa, 2016)
Shannoniella cuspidata Townsend, 1939 is redescribed and S. setinervis sp. nov. (Brazil, State of Rio de Janeiro) is newly described as its putative sister taxon, thereby allowing for a strict definition of the genus Shannoniella Townsend, 1939 through explicit synapomorphies. An identification key is provided.